Study of Some Trade Related Aspects of the Participation of Several Indian Scientists in the Drug Discovery Program of the National Cancer Institute (USA)¶ - Shrivastava, A.K.; Singh, D. (Asian Journal of Chemistry, 2010)
A case study of trade related aspects of the participation of a school of several Indian Scientists during the last 25 years in anticancer and/or anti-HIV drug discovery program of the National Cancer Institute (NCI) of USA has been carried out. The research work of the case was duly funded by Indian agencies viz., CSIR and UGC besides involvement of a number of government employees and assets, no trade related aspects were considered. The study reveals that the NCI (USA) continuously gained experience, knowledge, more power of purchase at the cost of Indian resources, money, material and technically expert skilled manpower and finally launch the products in the world market including India a targeted potential customers. Despite of significant contribution from Indian side the financial returns were extremely meager. In view of the double drain of Indian resources, development of awareness of trade related aspects of intellectual property rights among scientists and research funding agencies including government protected trade related concepts of scientific and medicinal research work in India needs urgent attention.